Linguagem, corpo e comunicação na arte de Eduardo Kac: em estudo a Holopoesia, a Arte da Telepresença e a Biopoesia - Fernández, Karina de Freitas Silva (2010)
The central aim of this work is the theoretical-reflective study of the Brazilian artist Eduardo Kac s work. Considering that his three main groups of artistic productions Holopoetry, Telepresence Art and Bio Art are part of his big project of searching for possible intersections of art, new technologies, and science, it is investigated how each one of those projects of art are organized in three axes: language, body and communication. Those three elements are articulated all the time and, with the development of the aforementioned projects, show how the artist is always investigating new forms of language, new ways of problematizing and representing the body in art and above all, new ways of communicating the distinct entities involved in each one of his artistic works. Therefore, through holopoetry the artist problematizes language in the three-dimensional space and the body as a reader of a new literature. Besides, communication, which is known by its intense information flow, is projected for the future. Concerning telepresence art, the study intendeds to research how the digital language, the body that is merged with machine and the interactive communication among interactors are articulated. Regarding transgenic art, it is quite relevant when it comes to the study of language that is converted into body and/or the body that becomes language, as well as the new biological body communicating and talking to human beings. The theoretical references for the given discussion comprehended the reading of texts produced by the artist himself, and investigators such as Hugues Marchal, Dan Collins, Simone Osthoff, Edmond Couchot, Claudia Gianetti, Derrick de Kerckhove, Arlindo Machado, Lucia Santaella, Emmanuel Lévinas, Gilles Delleuze, Jacques Derrida, Umberto Eco, and others who have helped us to follow the evolution of Eduardo Kac s works